Valoração socioambiental em áreas de preservação permanente no Rio do Sal em Aracaju/SE - Nadalini, Ana Carolina Valerio (2013)
This dissertation main goal is to contribute to the ecosystem services valuation improvement from a social environmental context. The hypothesis adopted is that the valuation process methodological improvement under the Ecological Economy perspective may help determine entitled compensation, in expropriation lawsuits concerning large areas with great natural resources and with biological significance such as permanent preservation areas, by including other value dimensions associated with the ecosystem services (social and ecological values, besides the economic value). It shows that valuation is one among other important instruments of political and environmental management and the improvement of this information may contribute to the decision making process and the sustainable use of natural resources. Therefore, the aspects of current environmental valuation are shown and a valuation guide using social and environmental indicators, which may be used in judicial valuations, is presented. In order to apply the proposed guide, a case study was conducted in an area situated on the right side bank of Rio do Sal, near the confluence of Sergipe river, within the city limits of Aracaju and Nossa Senhora do Socorro, covering one of the last portions of mangrove and wetlands, and where a housing project by the city of Aracaju is under way. The obtained values may still be used by prosecutors to take action related to environmental management.